Influence of methadone on the anticonvulsant efficacy of valproate sodium gabapentin against maximal electroshock seizure in mice by regulation of brain MDA TNF-α - Moradi Jafari, Ali; Hassanpourezatti, Majid (Frontiers in Neurology, 2022)
Methadone is the most frequently used opioid therapy worldwide, with controversial effects on oxidative stress homeostasis. This study investigated the effects of co-administration of methadone (0.1, 0.3, 1 and 3 mg/kg, i.p.) and valproate sodium (300 mg/kg, i.p.) or gabapentin (50 mg/kg, i.p.) in the mouse maximal electroshock (MES)-induced seizure model. Adverse-effect of drugs was assessed in the chimney test. The levels of tumor necrosis factor-alpha (TNF-α) and malondialdehyde (MDA) contents were measured in mice brains. Administration of methadone alone resulted in a significant reduction in the duration of hind limb extension (HLE) than in the control group. Pre-treatment with methadone at doses of 0.1 and 0.3 mg/kg, i.p., decreased, and at doses of 1 and 3 mg/kg, i.p., had an increasing effect on anticonvulsant efficacy of gabapentin. Pre-treatment with all doses of methadone decreased the valproate anticonvulsive efficacy. At doses of 1 and 3 mg/kg, i.p., methadone per se increased brain MDA level after MES-induced seizure. Administration of methadone (0.3 mg/kg, i.p.) enhanced and at 3 mg/kg decreased gabapentin effect on brain MDA level, but co-treatment of them did not lead to further increase of MDA. Methadone at 0.3 to 3 mg/kg enhanced sodium valproate’s effect on MDA levels in the brain, but at all doses significantly potentiated its effect on brain TNF-α level. The drugs did not produce any side effects on motor coordination in experimental animals. In conclusion, methadone showed different influences on anticonvulsant actions of gabapentin and valproate, through regulation of brain levels of MDA, and TNF-α.